PERAN GURU DALAM MENUMBUHKAN SUASANA PEMBELAJARAN KONDUSIF PADA ANAK USIA 5-6 TAHUN - Wardani, Siska Setia; Ali, Muhammad; Endang, Busri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to describe the role of teachers in fostering a conducive learning atmosphere. The subjects were 2 teachers in B1 TK Barunawati Pontianak Barat. This research uses descriptive method with qualitative research form. Data collection in this study used direct observation, interview, and documentation. After the data collected, test data to then drawn a conclusion. Based on the research that has been done, it can be concluded that; (1) Providing motivation by teachers in fostering a conducive learning atmosphere in Barunawati West Pontianak kindergarten is good for the creation of conducive learning atmosphere. (2) The guidance done by the teacher in fostering the conducive learning atmosphere in TK Barunawati Pontianak Barat is good for conducive learning (3) The exercises given by the teacher in fostering conducive learning atmosphere in B1 TK Barunawati Pontianak West is good for the conducive atmosphere of conducive learning. (4) assessment conducted by teachers in fostering a conducive learning atmosphere in kindergarten Barunawati West Pontianak is good.Keywords: Teacher's Role, Conducive Learning